Kejadian Balantidiosis pada Babi Landrace (A CASE STUDY OF BALANTIDIOSIS IN LANDRACE SWINE ) - Winaya, Ida Bagus Oka; Berata, I Ketut; Apsari, Ida Ayu Pasti (Jurnal Veteriner; Vol 12 No 1 (2011), 2012)
The aim of the study was to identify the incidence of balantidiosis in landrace pigs. A total of 60 pigswere examined at Faculty of veterinary medicine, Udayana University between January 2007 and January2008. Seven out of go pigs showed cahexia and diarrhoea . Macroscopic changes were observed, such as: thecolon was fully distended with gas and slight peritonitis,whereas microscopic examination revealed thepresence of Balantidium coli trophozoites and cysta within the intestinal mucosa. Additionally, enteritiskatarrhalis, slight hemorrhagis, erosin and pseudomembranous inflammation with lymphocytes andpolymorphonuclear cells were also noted.
Keywords: Balantidium coli, colon, Swine, necrotic, inflammation